EFL Pre-Service Teacher Trainees’ Perceptions on Developing Pupils’ Creativity - Rahmawati, Neng Emma; Hakim, Lystiana Nurhayat; Solihati , Tri Agustini (JET ADI BUANA, 2025)
Creativity is recognized as a critical 21st-century skill, particularly in English as a Foreign Language (EFL) education. While fostering creativity in language learning is widely acknowledged, limited research has explored how EFL pre-service teachers perceive and apply creativity in their cici4d teaching. This study investigated the perceptions of 123 EFL pre-service teachers who had completed a teaching practicum, focusing on their understanding of creativity, strategies for fostering it, and classroom practices. A quantitative cross-sectional survey was conducted using a 24-item Likert-scale questionnaire adapted from validated instruments, and the data were analyzed using descriptive statistics. The total mean score was 52.09, indicating generally positive perceptions but with considerable variation among individuals. Higher scores were recorded for practical strategies such as questioning techniques, collaboration, and adapting lessons to student interests. In comparison, lower scores were found for recognizing contextual factors and cici4d utilizing technology creatively. Overall, the findings suggest that while pre-service teachers value creativity, their understanding remains more product-oriented and expressive, with limited integration of higher-order thinking, contextual awareness, and technology as a strategic tool in fostering creativity.